Testing eco‐evolutionary predictions using fossil data: Phyletic evolution following ecological opportunity. (16th September 2019) - Voje, Kjetil Lysne
Abstract: Fossil sequences provide observations of phenotypes within a lineage over time and represent essential data for increasing our understanding of phyletic evolution beyond microevolutionary timescales. I investigate if fossil time series of the diatom Stephanodiscus niagarae / yellowstonensis follow evolutionary dynamics compatible with hypotheses for how the adaptive landscape changes when a population enters a new environment. The lineage—which has a remarkably detailed stratigraphic record—invaded Yellowstone Lake immediately after recession of ice from the basin 14, 000 years ago. Several phyletic models portraying different types of evolutionary dynamics—both compatible and not compatible with changes in the adaptive landscape following ecological opportunity—were fitted to the fossil times‐series of S. niagarae / yellowstonensis . Different models best describe the three analyzed traits. Two of the models (a new model of decelerated evolution and an Ornstein–Uhlenbeck model) capture trait dynamics compatible with an event of ecological opportunity, whereas the third model (random walk) does not. Entering a new environment may accordingly affect trait dynamics for thousands of years, but the effects can vary across phenotypes. However, tests of model adequacy reveal shortcomings in all three models explaining the trait dynamics, suggesting model development is needed to more fully understand the phyletic evolution in S. niagarae / yellowstonensis .